Monitoring the reduction of UO3 thin film by hydrogen atoms using valence-level spectroscopy: correlating the U5f1 signal to surface hydroxyls - El Jamal, G.; Gouder, T.; Eloirdi, R.; Jonsson, M.; Idriss, H. (Frontiers in Fuels, 2023)
The reaction of a UO3 thin film with atomic hydrogen was studied by He(II) Ultraviolet Photoelectron Spectroscopy (UPS) in the temperature range 190-300 K. UO3 reduction was observed instantaneously once in contact with hydrogen atoms at 10 -7 torr. The reduction was manifested by the presence of U5f 1 electrons, He(II) UPS, at about 1.5 eV below the Fermi Level. Based on the peak characteristics, the valence band shape (composed largely of O2p orbitals in addition to some contribution from U6d and U5f orbitals), and X-ray photoelectron spectroscopy (XPS) U4f lines, the reduction of U 6+ in UO3 results in the formation of U 5+ cations only and was largely limited to those on the surface. Associated with the reduction was the formation of surface hydroxyls (-OH species) due to the transfer of a proton of the hydrogen atom (H . ), to surface oxygen ions, while the electron (of H . ) is transferred to a U5f orbital. The pseudo-first-order rate constant of the initial rate of reduction at 10 -7 torr and 190 K was found to be about 0.01 s -1 . Qualitative analysis of the valence band before and after reduction indicates that O2p hybridization with U6d and U5f orbitals leads to well-distinct features that are characteristic of UO3, U2O5 and UO2. These features, which were quantitatively reversed during the redox process, help in further assessing the stoichiometry of a given binary uranium oxide.